GE_GERICHTE C/2625/2015 vom 12. Dezember 2016 - GE Cour de justice (2016)
DIMINUTION DE LOYER ; DÉFAUT DE LA CHOSE ; VOLONTÉ RÉELLE ; DOMMAGES-INTÉRÊTS ; INTÉRÊT MORATOIRE | CO.18; CO.259a; CO.259d; CO.259e; CC.8